20 HEPRAN Prevalence of Leprosy in Nkanu West LGA of Enugu State, Nigeria (2005-2015) - Ugwuoke, Anthony; Ani , N. R (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
The prevalence of leprosy is decreasing in many parts of the world following a global campaign to reduce the prevalent rate to less than 1/10,000 population. Since, leprosy has high socioeconomic and public heath burden, Nigeria has adopted the campaign strategies and has achieved the target. However, there are no data on the prevalence and rate of leprosy based on age and gender in Nkanu West Local Government Area (LGA) of Enugu state which necessitated this study. Four research questions were posed to guide the study. Ex-post-facto design was employed in the census study involving 26 patients that reported in the health facilities in the LGA. The data obtained using the researcher’s self-developed Leprosy Record Review Proforma (LRReP) were analyzed using frequency and percentage. Results showed that the prevalence of leprosy was highest in 2012 with 5 cases (19.23%) and least in 2010 with zero case (0.00%). Prevalence rates of leprosy in Nkanu West LGA (2005-2015) were within the international elimination target of below 1/10000. Prevalence rate of leprosy was highest (0.3/10000 population) in 2012 and lowest (0.0/10000 population) in 2010. The cumulative prevalence rate from 2005-2015 was 1.3/10000 population. Leprosy was most common among those aged 41 years and above 16 (61.53%) and least among those aged 0-20 years with one (3.85%) case. More male 14 (53.85%) than female 12 (46.15%) sought treatment for leprosy during the period. Based on the results, the researcher made some recommendations which included carrying out health promotion in the communities to sensitize them on the cause and mode of transmission of leprosy. There could also be health promotion on the best treatment option which was available in the health facilities in the LGA